1982
DOI: 10.1038/bjc.1982.5
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine enhancement of cyclophosphamide antitumour activity

Abstract: Summary.-Male DBA2 mice were given 106 P-388 leukaemic cells i.p. and cimetidine (CMT) at 100 mg/kg 1 day for 10 days, or as a single 100mg/kg injection 30 min before cyclophosphamide (CTX). CMT significantly prolonged the survival of groups of mice receiving 50, 100 and 200 mg/kg of CTX 3 days after tumour inoculation.Median survival increased by 5-5 days (P <0-05), 10 days (P <0.05) and 13 days (P < 0.05) respectively. The addition of CMT had the effect of roughly doubling the CTX dose, without increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A series of reports describe regressions induced by immunologic methods in clinical trials (BCG, im mune RNA, autologous tumour cells, polymerized antigen with adjuvant, interferons and others) [13]. Cimetidine, widely used as an anti-ulcer agent, is known to affect H2 receptors on the surface of various target cells [6,19], It has been shown to enhance mitogen responsiveness of human lymphocytes [10], enhance skin test reactivity to a number of antigens [1], to stimulate antibody synthesis [2,7,8], and to extend life of tumour-bearing animals [11], Dorr and Alberts [5] found that cimetidine could enhance cyclo phosphamide antitumour activity. In 1981, successful immunotherapy of tumours in mice with cimetidine, associated with a decrease in suppressor cell levels was reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…A series of reports describe regressions induced by immunologic methods in clinical trials (BCG, im mune RNA, autologous tumour cells, polymerized antigen with adjuvant, interferons and others) [13]. Cimetidine, widely used as an anti-ulcer agent, is known to affect H2 receptors on the surface of various target cells [6,19], It has been shown to enhance mitogen responsiveness of human lymphocytes [10], enhance skin test reactivity to a number of antigens [1], to stimulate antibody synthesis [2,7,8], and to extend life of tumour-bearing animals [11], Dorr and Alberts [5] found that cimetidine could enhance cyclo phosphamide antitumour activity. In 1981, successful immunotherapy of tumours in mice with cimetidine, associated with a decrease in suppressor cell levels was reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike Dorr & Alberts (1982), we were unable to demonstrate any enhancement of cyclophosphamide antitumour activity by cimetidine, and this discrepancy may be attributed to the use of a different tumour system, or the fact that Dorr & Alberts administered the drug i.p. directly to the site of the tumour.…”
mentioning
confidence: 58%
“…Although the mechanism of H2-receptor involvement in anti-tumour drug activity remains obscure, Gifford et al (1981) and Osband et al (1981) have suggested inhibition of suppressor-cell function by cimetidine, while Dorr & Alberts (1982) explain their results through an interference with the microsomal metabolism of compounds utilizing the P450 system as previously suggested by Pelkonen & Puurunen (1979, 1980, or via a change in liver blood flow as demonstrated for cimetidine by Feely et al (1981).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition animal studies have shown that cimetidine can enhance the antitumour activity of cyclophosphamide approximately two-fold (Dorr & Alberts, 1982), an effect presumed to be due to greater concentrations of active metabolites. Increased plasma concentrations of drugs given with cimetidine have been attributed to both inhibition of hepatic microsomal metabolism (Henry et al, 1981; Time (min) Figure 6 Mean plasma concentrations of 5FU following oral administration before (o *) and after (0oo) cimetidine for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%